2010
DOI: 10.1186/1471-2318-10-21
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioural therapy in elderly type 2 diabetes patients with minor depression or mild major depression: study protocol of a randomized controlled trial (MIND-DIA)

Abstract: BackgroundThe global prevalence of diabetes among adults will be 6.4% in 2010 and will increase to 7.7% by 2030. Diabetes doubles the odds of depression, and 9% of patients with diabetes are affected by depressive disorders. When subclinical depression is included, the proportion of patients who have clinically relevant depressive symptoms increases to 26%. In patients aged over 65 years, the interaction of diabetes and depression has predicted increased mortality, complications, disability, and earlier occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
9
0
2
Order By: Relevance
“…Other investigators are currently examining physical activity as part of depression treatment among individuals with T2DM (Petrak et al, 2010). In the MIND-DIA trial, elderly persons (age 65 to 85) will be randomized into one of three arms: (1) group CBT delivered by trained psychologists who focus on strategies to overcome depression and diminish diabetes-related distress in addition to the use of pedometers to increase physical activity, (2) manualized guided self-help intervention or (3) treatment as usual.…”
Section: Treatments For Depression Among Individuals With Diabetesmentioning
confidence: 99%
“…Other investigators are currently examining physical activity as part of depression treatment among individuals with T2DM (Petrak et al, 2010). In the MIND-DIA trial, elderly persons (age 65 to 85) will be randomized into one of three arms: (1) group CBT delivered by trained psychologists who focus on strategies to overcome depression and diminish diabetes-related distress in addition to the use of pedometers to increase physical activity, (2) manualized guided self-help intervention or (3) treatment as usual.…”
Section: Treatments For Depression Among Individuals With Diabetesmentioning
confidence: 99%
“…The prevalence of diabetes has been increasing rapidly. 1 In 2010, the global prevalence rate of adult diabetes was 6.4%, and it is projected that it would increase to 7.7% by 2030. 1 The incidence of depression in patients with diabetes has been significantly higher than that of the general population.…”
Section: Introductionmentioning
confidence: 99%
“…1 In 2010, the global prevalence rate of adult diabetes was 6.4%, and it is projected that it would increase to 7.7% by 2030. 1 The incidence of depression in patients with diabetes has been significantly higher than that of the general population. [2][3][4] Depression and depression-related symptoms increase medical costs, reduce quality of life of patients, and increase risk of complications and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported that health improvements can occur with effective CBT programs for depression and stress in persons with diabetes [20, 45]. In addition, other studies are using a CBT approach to treat mild and major depression in persons with diabetes [46, 47]. …”
Section: Introductionmentioning
confidence: 99%